Embodied musical empathy from Vivaldi to Puccini and beyond (Materiali di Estetica. Terza serie, 2025)
This study explores the relationship between music, the body and perception, proposing an addition to the reductionist approach of musical analysis. Using examples from the instrumental and operatic repertoire, it shows how music elicits spontaneous sensory and motor responses, suggesting a possible link between the action-perception cycle and musical empathy. A holistic view of music is proposed that integrates formal analysis with embodied experience, emphasising the role of emotion and musical affordances.
Keywords: affective affordances; embodied music; sense-making; extended mind